Transformasi Tradisi Sorogan menjadi Praktik Literasi Sekolah di Ma Ali Maksum Yogyakarta - Wahyuliani, Eni; Ichsan, Ichsan; Hardianto, Ilham (Lembaga Teewan Journal Solutions, 2026)
Indonesia's School Literacy Movement (Gerakan Literasi Sekolah/GLS) has primarily been implemented through habitual reading activities, while the integration of pesantren pedagogical traditions into literacy programs remains limited. This study examines the transformation of the sorogan tradition into a school literacy practice through the Sorogan Buku Program at MA Ali Maksum Yogyakarta, its implementation, and its implications for strengthening students' literacy culture. A qualitative case study approach was employed. Data were collected through observation, in-depth interviews, and document analysis, then analyzed using the Miles and Huberman interactive model. Data triangulation ensured the trustworthiness of the findings. The results reveal that the sorogan tradition has been successfully transformed into a school literacy practice while preserving its pesantren pedagogical values. The Sorogan Buku Program is implemented through systematic planning, implementation, monitoring, and evaluation, creating a literacy cycle based on guided learning, oral presentation, and constructive feedback. This transformation enhances students' reading habits, comprehension and communication skills, independent learning, and academic responsibility. The study contributes to the conceptualization of sorogan as a literacy-based pedagogical model that supports the development of the School Literacy Movement in pesantren-based madrasahs.